Full-moon chanting as transformative Buddhist education: integrating saddhā and moral values formation among Buddhist students - Wulia Purnama Sari; Ayu Andriyaningsih; Sidartha Adi Gautama (Universitas Sebelas Maret, 2025)
This study examines the role of Full Moon Puja Bhakti as a form of transformative Buddhist education that integrates saddhā (faith) and moral values formation among Buddhist students in East Lampung, Indonesia. In Buddhist teaching, devotional practices such as Puja Bhakti are not only rituals of reverence but also pedagogical spaces that transmit ethical values, strengthen faith, and cultivate spiritual discipline. Within the school and community context, Full Moon observances allow students to internalize Buddhist teachings through chanting, reflection, and collective devotion, fostering a sense of identity and moral responsibility. The research employed a quantitative approach using survey methods. Data were collected through validated questionnaires distributed to Buddhist students actively participating in Puja Bhakti, involving 207 students. Data analysis used the SPSS 26 application. Regression analysis was applied to identify the effect of ritual participation on the strengthening of saddhā and the development of moral values. Findings indicate that Full Moon Puja Bhakti significantly reinforces faith and shapes students' ethical conduct. The practice is an integrative educational tool that unites spiritual devotion with character building. As a result, Full Moon Puja Bhakti can be considered an effective pedagogical model for promoting transformative Buddhist education, ensuring the preservation of saddhā and ethical values within contemporary youth communities.